2020
DOI: 10.3897/rrpharmacology.6.49413
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of mesenchymal stem cells secretome as a basis for cell-free therapeutic approach

Abstract: Mesenchymal stem (stromal) cells (MSCs) are self-renewing, cultured adult stem cells which secrete a complex set of multiple soluble biologically active molecules such as chemokines, and cytokines, cell adhesion molecules, lipid mediators, interleukins (IL), growth factors (GFs), hormones, micro RNAs (miRNAs), long non-coding RNAs (lncRNAs), messenger RNAs (mRNAs), exosomes, as well as microvesicles, the secretome. MSCs of various origin, including adipose-derived stem cells (ASCs), bone marrow derived mesench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 119 publications
0
19
0
Order By: Relevance
“…In this study, we harnessed the reparative, regenerative and immunomodulatory potential of MSCs-secretome to promote proper vascular growth in ischemic retinas and prevent pathological neovascular formation. Several studies have shown that the therapeutic effects of MSCs can be associated with soluble paracrine factors and show even better tissue repair than the cells themselves ( Uemura et al, 2006 ; Timmers et al, 2011 ; Liang et al, 2014 ; Pankajakshan and Agrawal, 2014 ; Pokrovskaya et al, 2020 ). MSCs-secretome has shown a low risk of toxicity, and immune rejection ( Baek et al, 2019 ) making it a promising therapeutic alternative for the treatment of IRs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we harnessed the reparative, regenerative and immunomodulatory potential of MSCs-secretome to promote proper vascular growth in ischemic retinas and prevent pathological neovascular formation. Several studies have shown that the therapeutic effects of MSCs can be associated with soluble paracrine factors and show even better tissue repair than the cells themselves ( Uemura et al, 2006 ; Timmers et al, 2011 ; Liang et al, 2014 ; Pankajakshan and Agrawal, 2014 ; Pokrovskaya et al, 2020 ). MSCs-secretome has shown a low risk of toxicity, and immune rejection ( Baek et al, 2019 ) making it a promising therapeutic alternative for the treatment of IRs.…”
Section: Discussionmentioning
confidence: 99%
“…The secretome may even fluctuate in response to various physiological changes and pathological circumstances. In general, MSC secretome is made up of a variety of growth factors, cytokines, and EVs that conferred its tissue repair and regenerative potential, mainly attributed to their capability to stimulate cell proliferation, formation of new blood vessels, and their immunomodulatory effects (Figure 3) [85,86].…”
Section: Secretomementioning
confidence: 99%
“…Stem Cells International (TNF-β1), IL-10, IL-12 p70, IL-13, IL-18 binding protein, IL-25, and IL-27) and proinflammatory cytokines (such as TNFα, interferon γ (IFN-γ), IL-1b, IL-6, IL-8, and IL-9) could be present. The impact of MSC secretome on the inflammatory process is usually governed by the balance of these anti-and proinflammatory cytokines [86]. For example, the destruction of pancreatic cells in autoimmune diabetes mellitus type 1 disease by proinflammatory cytokines, including TNF-α, IFN-γ, and IL-1b, could be reversed by treating the primary islet cells with MSC secretome containing significantly elevated levels of anti-inflammatory cytokines (IL-4 and IL-10), resulted in the prevention of cell apoptosis and improvement in insulin secretion [99].…”
mentioning
confidence: 99%
“…Many other inflammatory mediators such as chemokines or growth factors produced by MSCs may exert different actions inside the tumor microenvironment involving both antitumor and pro-tumor activity [38]. The conditioned medium of MSCs contains an enormous quantity of molecules (cytokines, chemokines, hormones and many other factors) with different biological activity that can also work together with exosomes/microvesicles produced by MSCs [39,40]. As reported by Mirabdollahi et al [41], the secretome of umbilical cord-derived mesenchymal cells can have an anticancer effect on MCF-7 tumor cells by inducing apoptosis in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%